Seasonal cues act through the circadian clock and pigment-dispersing factor to control EYES ABSENT and downstream physiological changes. - Hidalgo, S.; Anguiano, M.; Tabuloc, C.A.; Chiu, J.C. (Current Biology, 2023)
Organisms adapt to seasonal changes in photoperiod and temperature to survive; however, the mechanisms by which these signals are integrated in the brain to alter seasonal biology are poorly understood. We previously reported that EYES ABSENT (EYA) shows higher levels in cold temperature or short photoperiod and promotes winter physiology in Drosophila. Nevertheless, how EYA senses seasonal cues is unclear. Pigment-dispersing factor (PDF) is a neuropeptide important for regulating circadian output rhythms. Interestingly, PDF has also been shown to regulate seasonality, suggesting that it may mediate the function of the circadian clock in modulating seasonal physiology. In this study, we investigated the role of EYA in mediating the function of PDF on seasonal biology. We observed that PDF abundance is lower on cold and short days as compared with warm and long days, contrary to what was previously observed for EYA. We observed that manipulating PDF signaling in eya+ fly brain neurons, where EYA and PDF receptor are co-expressed, modulates seasonal adaptations in daily activity rhythm and ovary development via EYA-dependent and EYA-independent mechanisms. At the molecular level, altering PDF signaling impacted EYA protein abundance. Specifically, we showed that protein kinase A (PKA), an effector of PDF signaling, phosphorylates EYA promoting its degradation, thus explaining the opposite responses of PDF and EYA abundance to changes in seasonal cues. In summary, our results support a model in which PDF signaling negatively modulates EYA levels to regulate seasonal physiology, linking the circadian clock to the modulation of seasonal adaptations.